RETRACTED: MicroRNA-27 Inhibits Autophagy and Promotes Proliferation of Multiple Myeloma Cells by Targeting the NEDD4/Notch1 Axis - Che, Feifei; Chen, Jiao; Wan, Chunqian; Huang, Xiaobing (Frontiers in Oncology, 2020)
Multiple myeloma (MM) is a malignant tumor disease that seriously affects the health of patients. Previous studies have shown the crucial role of autophagy in the development of MM. Therefore, the study aimed to study the effect of miR-27 on autophagy in MM via NEDD4/Notch1 axis. RT-qPCR or western blot analysis was used to detect the expression of miR-27, NEDD4, and Notch1 in bone marrow tissues and CD138+ plasma cells of patients and MM cells. After gain- and loss-of-function assays in MM cells, proliferation and invasion were assessed by clone formation and Transwell assays. Meanwhile, expression of autophagy-related proteins was measured by western blot analysis, followed by evaluation of autophagosomes and autophagic flow. The targeting relationship was evaluated by luciferase reporter assay, whereas the binding of NEDD4 to Notch1 protein was analyzed by co-immunoprecipitation. The ubiquitination level of Notch1 protein was detected. A nude mouse tumor model was established to determine the role of miR-27 in MM in vivo. miR-27 and Notch1 upregulation and NEDD4 downregulation were observed in bone marrow tissues and CD138+ plasma cells of patients and MM cells. miR-27 negatively targeted NEDD4, while NEDD4 could specifically bind to Notch1 protein to increase Notch1 ubiquitin degradation in MM cells. miR-27 or Notch1 overexpression or NEDD4 silencing diminished autophagy, but enhanced proliferation and invasion of MM cells. miR-27 upregulation promoted the formation of subcutaneous tumor in nude mice. Collectively, miR-27 elevated Notch1 expression by targeting NEDD4 and promoted the development of MM by inhibiting cell autophagy, which provides a new idea and basis for MM treatment.